Patient Privacy, Consent, and Identity Management in Health Information Exchange Issues for the Military Health System - Hosek, Susan D. (RAND Corporation, 2013)
As a step toward improving its health information technology (IT) interoperability, the Military Health System is seeking to develop a research roadmap to better coordinate health IT research efforts, address IT capability gaps, and reduce programmatic risk for its enterprise projects. This report identifies gaps in research, policy, and practice involving patient privacy, consent, and identity management that need to be addressed to improve the quality and efficiency of care through health information exchange.